Siri' na Pacce Character Value and Learning Outcomes of Pancasila and Civic Education through Contextual Learning - Vivi Kasvita; Rosleny Babo; Muhajir Muhajir (Pedagonal : Jurnal Ilmiah Pendidikan, 2022)
This study aims to determine the value of the character of local wisdom Siri' na Pacce and the learning outcomes of fifth grade students in Cluster 33, Ganra District, Soppeng Regency in PPKn learning through the application of Contextual Learning Models. This type of research is quantitative research with a quasi-experimental design. The research design used is the Nonequivalent Control Group Design. The samples in this study were fifth grade students at SDN 81 Belo as the experimental class and fifth grade students at SDN 80 Paomallimpoe as the control class. The data collection technique used is taking student learning test results, the average acquisition value of student material understanding is 84.84. While the average acquisition value of student characters is 79.54. Based on the results of the questionnaire given to students, it was proven that in general the character of students was active, this was evidenced by the results of data processing that of 11 students there were 72.73% (8 of 11 students) were in the active criteria. In the experimental class there was an increase in student Civics learning outcomes after following the Contextual Learning Model at SDN 81 Belo. This is based on the statistical table the average score of pre-test Civics learning outcomes is 56.36 and the average post-test Civics learning outcomes is 84.84. While the control class at SDN 80 Paomallimpoe in general, student learning outcomes are less, this is based on the results of the analysis of the average student learning outcomes in the pre-test 60.74 and the average student learning outcomes in the post-test 62.21. This hypothesis test proves that Ho is rejected and Ha is accepted, so there is a significant effect of Contextual Learning Model on the character and learning outcomes of student Civics. This research is expected that the Contextual Learning Model can be used as one of the learning strategies in schools to improve character values and student learning outcomes.